Integrating acquired knowledge development in business administration with Islamicisation: the Ulū al-Albāb approach - Mhd. Sarif, Suhaimi (2013)
This paper explores the challenges and opportunities from using the Ulū al-Albāb (men of the understanding) approach as a mean to integrate acquired knowledge in business administration with the Islamicisation process. Ulū al-Albāb approach integrates individual and collective physical, intellectual and spiritual dimensions to produce intellectual in business administration specifically that are thoughtful, conscious, and dynamic in the contemporary world. The conventional paradigm emphasises on physical and material aspects with some superficial inclusion of spirituality, which contributes to imbalance human growth in the academic field. The significant gap between conventional and the Ulū al-Albāb approach is the emphasis on the understanding about the essence of life. The study used an opinion survey with selected academicians from selected public universities in Malaysia who are familiar with conventional academic development and the Islamic education scheme to answer “what are the challenges and opportunities for implementing holistic academic development approach?” There is no right or wrong answer. Respondents are free to express their views. The results show that the informants perceived that the Ulū al-Albāb approach is commendable insights to nurture academics into holistic and dynamic modern academic development. The challenges include ethical issues intensity, individual factors, organizational factors, and industrial factors. Despites the challenges, respondents suggested that the opportunities can be obtained from good relationship among colleagues/co-workers, professional networking, and pressures from the stakeholders. However, the views of the academicians are not comprehensive and rigorous without the views from other stakeholders. Nevertheless, higher education policy makers can apply the Ulū al-Albāb approach into the existing academic development programs.